Teachers’ involvement and learning in a lesson study - Ponte, João Pedro da (2014)
The aim of this study is to analyse the way a group of basic education teachers got involved in a lesson study and their views, as they discuss the features of tasks, students’ expected difficulties and how to conduct exploratory work in the mathematics classroom. The conceptual framework draws on notions of task design and considers the features of lesson study. Data collection was made through a research journal made by one of the authors in the role of observer, video recording with transcription of the sessions, teachers’ written reflections and interviews. The results underscore the value of focusing on students’ reasoning in working in mathematical tasks as well as the need to address affective issues, regarding the way teachers are invited to become involved and participate in lesson studies.